2021
DOI: 10.5812/gct.110658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroalcoholic Extract of Ephedra major, Momordica charantia, and Resveratrol on Cytotoxicity and Caspase-3 Genes Expression Level in MCF-7 Breast Cancer Cell Line

Abstract: Background: To increase the therapeutic effect of drugs to combat diseases, combination therapy with current chemical drugs and new medicines derived from medicinal plants is necessary. Objectives: The present work aimed to investigate the effect of hydroalcoholic extract of two medicinal plants, Ephedra major and Momordi cacharantia (Carla), and resveratrol drug on cell viability and expression levels of caspase-3 gene in MCF-7 cell line. Methods: In this experimental study, the hydroalcoholic extraction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Therefore, algae may have been used in cancer treatment and pharmaceutical industry. In our previous study, Ephedra major extract had been shown to influence cell viability and Caspase gene expression in treated MCF7 cell line (12). The activation and high expression of Caspase 3 gene have also been detected to influence the induction of apoptosis process in cancer cell (29,30).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, algae may have been used in cancer treatment and pharmaceutical industry. In our previous study, Ephedra major extract had been shown to influence cell viability and Caspase gene expression in treated MCF7 cell line (12). The activation and high expression of Caspase 3 gene have also been detected to influence the induction of apoptosis process in cancer cell (29,30).…”
Section: Discussionmentioning
confidence: 92%
“…Two penicillin and streptomycin antibiotics (Sigma Aldrich, Germany) from Passage 17 were used for performing all experiments under a humidified air atmosphere. MTT reagent was used to carry out the cell viability assay adopting the colorimetric method (11,12).…”
Section: Cell Culture and Cell Viability Assaymentioning
confidence: 99%